2017
DOI: 10.1002/cbdv.201700105
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis‐Inhibitory and Cytotoxic Activities of Limonoids, Alkaloids, and Phenolic Compounds from Phellodendron amurense Bark

Abstract: Four limonoids, 1 - 4, five alkaloids, 5 - 9, and four phenolic compounds, 10 - 13, were isolated from a MeOH extract of the bark of Phellodendron amurense (Rutaceae). Among these, compound 13 was new, and its structure was established as rel-(1R,2R,3R)-5-hydroxy-3-(4-hydroxy-3-methoxyphenyl)-6-methoxy-1-(methoxycarbonylmethyl)indane-2-carboxylic acid methyl ester (γ-di(methyl ferulate)) based on the spectrometric analysis. Upon evaluation of compounds 1 - 13 against the melanogenesis in the B16 melanoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 54 publications
(82 reference statements)
0
16
0
Order By: Relevance
“…Four "naphthalene-devoid" tetra-and dihydroisoquinolines, named ealaines A−D (18−21), were isolated from the Congolese plant Ancistrocladus ealaensis. 32 Akihisa et al 33 isolated noroxyhydrastinine Corydalis tomentella [28] 402 Oleracein E Portulaca oleracea [31] 403 Pipermullesine B Piper mullesua [108] 404 Pipermullesine C Piper mullesua [108] 405 Delavatine A Incarvillea delavayi [109] 406 Neotatarine Acorus calamus [110] Cryptocarya griffithiana, and Dehaasia longipedicellata, over the past 5 years. [34][35][36][37][38][39] (+)-N-Methylisococlaurine (24) also was found in Cryptocarya species and (−)-N-methylcoclaurine (25) was identified in the rhizomes of Sinomenium acutum in 2014.…”
Section: 4′-oo-didemethylancistrocladinium a (A/b)mentioning
confidence: 99%
See 2 more Smart Citations
“…Four "naphthalene-devoid" tetra-and dihydroisoquinolines, named ealaines A−D (18−21), were isolated from the Congolese plant Ancistrocladus ealaensis. 32 Akihisa et al 33 isolated noroxyhydrastinine Corydalis tomentella [28] 402 Oleracein E Portulaca oleracea [31] 403 Pipermullesine B Piper mullesua [108] 404 Pipermullesine C Piper mullesua [108] 405 Delavatine A Incarvillea delavayi [109] 406 Neotatarine Acorus calamus [110] Cryptocarya griffithiana, and Dehaasia longipedicellata, over the past 5 years. [34][35][36][37][38][39] (+)-N-Methylisococlaurine (24) also was found in Cryptocarya species and (−)-N-methylcoclaurine (25) was identified in the rhizomes of Sinomenium acutum in 2014.…”
Section: 4′-oo-didemethylancistrocladinium a (A/b)mentioning
confidence: 99%
“…40 Berbithine (26) and 6-( [1,3]dioxolo[4,5-g]isoquinoline-5-carbonyl)-2,3-dimethoxybenzoic acid methyl ester (27) were isolated from the rhizome of Coptis chinensis. 41 In 2018, several benzylisoquinoline alkaloids, including 24, 25, norcolaurine-4′-O-glucoside (28), N-methylhigenamine (29), norcoclaurine-6-O-glucoside (30), norcoclaurine (31), argemexirine (32), lotusine (33), isococlaurine (34), armepavine (35), 6-demethy-4′-methyl-N-methylcoclaurine (36), coclaurine (37), N-nor-O-methylarmepavine (38), isococlaurine-5′-Opentoside (39), and coclaurine-5′-O-pentoside (40) were identified from P. nelumbinis through UPLC-ESI-QTOF-MS. 30 Subsequently, juzirine (41) was identified from the aerial parts of Leonurus japonicus. 42 (R)-(+)-1-Benzyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline (42) from P. oleracea showed anti-inflammatory and β2-adrenergic receptor agonist activities.…”
Section: 4′-oo-didemethylancistrocladinium a (A/b)mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it can inhibit its proliferation and migration [33]. Interestingly, research revealed that limonin has strong inhibitory activity on melanin production in B16 melanoma cells, but has weak cytotoxicity on B16 melanoma cells [34].…”
Section: Pharmacologymentioning
confidence: 99%
“…Natural and synthetic aza-heterocycles represent an important class of organic compounds [1][2][3][4][5]. Among the large number of aza-heterocycles available, pyridones and quinolones, both of which have a common six-membered aza-framework, exhibit a wide range of pharmacologically important activities ( Figure 1) [6][7][8][9][10]. Therefore, various methods for the preparation of structurally diverse pyridones and quinolones have been studied in detail [6,[11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%